2018
DOI: 10.1016/j.devcel.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Polarity of Neuronal Membrane Traffic Requires Sorting of Kinesin Motor Cargo during Entry into Dendrites by a Microtubule-Associated Septin

Abstract: In the originally published version of this article, the landing rate units in Figures 4A, 6A, and 7E, as well as in the Quantification and Statistical Analysis section of the STAR Methods under the ''In Vitro Motor Motility'' subheading, were erroneously noted as ''events mm À1 s À1 '' rather than as ''events mm À1 min À1 '' due to mistaken changes made at the proof stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 0 publications
3
52
0
Order By: Relevance
“…We tested if SEPT9 impacts lysosome traffic in primary rat embryonic hippocampal neurons. In early stages of neuronal morphogenesis, SEPT9 is present in the developing axon before it becomes enriched on dendritic microtubules (Karasmanis et al, 2018). In the axons of these cells, which consist of unidirectional plus endout oriented microtubules, we found that SEPT9 was enriched more than two-fold in LAMP1positive endolysosomes compared to Rab5-containing early endosomes (Fig.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…We tested if SEPT9 impacts lysosome traffic in primary rat embryonic hippocampal neurons. In early stages of neuronal morphogenesis, SEPT9 is present in the developing axon before it becomes enriched on dendritic microtubules (Karasmanis et al, 2018). In the axons of these cells, which consist of unidirectional plus endout oriented microtubules, we found that SEPT9 was enriched more than two-fold in LAMP1positive endolysosomes compared to Rab5-containing early endosomes (Fig.…”
Section: Introductionmentioning
confidence: 68%
“…This scaffolding function may facilitate cooperative assembly of dynein-dynactin into the nanodomains of motor teams, which have been observed on lipid microdomains and microtubules (Cella Zanacchi et al, 2019;Rai et al, 2016) Among the members of the septin family of GTPases, SEPT9 is unique in possessing a faster GTPase activity and a dimerization interface, which is characterized by nucleotide-dependent plasticity (Castro et al, 2020;Zent and Wittinghofer, 2014). Additionally, SEPT9 has been reported to function and localize independently of its heteromeric partners as the central subunit of the octameric SEPT2/6/7/9 complex (Estey et al, 2010;Karasmanis et al, 2018). Our results indicate that SEPT9 interacts with dynein independently of SEPT2/6/7, but do not rule out the possibility that SEPT9 functions in a complex with SEPT2/6/7 on lysosomal membranes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SEPT9 isoforms associate with the SEPT7 subunits of the hetero-hexameric SEPT7-SEPT6-SEPT2-SEPT2-SEPT6-SEPT7 complex, but longer SEPT9 isoforms might be preferred over shorter ones (14,15,20). Interestingly, in some cell types and processes, SEPT9 proteins appear to localize and function independently of SEPT2/6/7 (19,27,28).…”
Section: Introductionmentioning
confidence: 99%